Use of Prothrombin Complex Concentrate in Patients during Heart Transplantation after Implantation of a Left Ventricular Mechanical Support System - Lomivorotov, V. V.; Shmyrev, V. A.; Deryagin, M. N.; Efremov, S. M.; Kornilov, I. A.; Chernyavsky, A. M. (Obshchai͡a︡ reanimatologii͡a, 2012)
Heart transplantation in patients after implantation of mechanical cardiac support devices entails an extremely high risk for perioperative bleeding. Recombinant activated coagulation factor VII is presently used to reduce the volume of bleeding in this patient group. There are parallel data on its administration-induced thromboembolic events in the literature. This paper describes a case of using a prothrombin complex concentrate in a patient during explantation of a left ventricular bypass system and subsequent orthotopic heart transplantation in the presence of significant hypocoagulation. At the end of a surgery, 1200 IU of the agent was used at a remaining bleeding rate of more than 1000 ml/hour. Within the first 24 hours after surgery, the rate of discharge drainage was less than 100 ml/hour. A control plain chest X-ray study revealed massive left-sided hydrothorax on day 2 postsurgery. The left pleural cavity was revised under thoracoscopic guidance and 1000 ml of blood clots were evacuated. Although the administration of prothrombin complex concentrate did not guard against re-intervention, its use seems a promising strategy in life-threatening bleedings in patients after explantation of mechanical cardiac support devices. Further multicenter investigations are required to determine the efficacy and safety of prothrom-bin complex concentration in cardiac surgery. Key words: Recombinant activated coagulation factor VII, prothrombin complex concentration, mechanical cardiac support device, orthotopic heart transplantation.